Thematic Hadith Understanding in West Sumatra: Kitab Himpoenan Hadis by Syekh Yunus Tuanku Sasak - Febriyeni Febriyeni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This article examines Syekh Yunus Tuanku Sasak (1879-1975) and elaborates on the characteristics of thematic hadith studies in his book, Himpoenan Hadith Book (1938). The book is one of the classic books of hadith in Arabic-Malay, which became the guideline in several Madrasah Tarbiyah Islamiyah in West Sumatra. Syekh Yunus Tuanku Sasak is a West Sumatran cleric active in da'wah and education activities. The background of writing this book is to fulfil the request of the leaders of Madrasah Tarbiyah Islamiyah in the West Pasaman environment to overcome the rampant debate in the community related to qunūt. This article uses a qualitative literature study method on the works of Syekh Tuanku Sasak and is supported by in-depth interviews with the descendants of Syekh Tuanku Yusuf in 2019. This research shows that Syekh Yunus Tuanku Sasak thematically describes the understanding of the hadith about qunūt by collecting all the traditions that allow and forbid qunūt, conduct criticism of sanad and matan, and use the